Characteristics of posterior circulation cerebral angiography from dizziness patients: a retrospective single-center cross-sectional study - Usman, Fritz Sumantri; Sagita, Noveline; Sastrawan, M. Gandhi; Vernandi, Andra; Kastilong, Merlin P.; Kurnia, Leny (International Journal of Research in Medical Sciences, 2024)
Background: This study aimed to analyze posterior circulation cerebral angiography characteristics in dizziness patients. Methods: This was an analytical retrospective cross-sectional study on medical records data performed at Pelni Hospital. Subjects with the main complaint of dizziness/vertigo who fulfill the criteria for vascular vertigo and underwent digital subtraction angiography (DSA) in 2023, were recruited. The exclusion criterion was incomplete medical records. Results: Two hundred and eighty-one subjects aged 14-79 years old were recruited. A total of 88.3% of subjects had abnormal DSA results, comprising posterior circulation abnormalities (hypoplasia/aplasia 11%, tortuous 40.2%, mild stenosis 8.9%, severe stenosis 16.7%, atherosclerosis 2.5%) and 42.8% of them had anterior circulation abnormalities. Older subjects tended to have tortuous vessels and abnormal anterior circulation. Females tended to have tortuous vessels (p<0.001) while males tended to have mild (p = 0.001) and severe stenosis (p = 0.002). Diabetes mellitus and cardiac disorders had significant associations with severe stenosis (p = 0.035 and 0.003, respectively) and anterior circulation abnormalities (p = 0.024 and 0.001, respectively). Subjects with dizziness tended to have hypoplasia or aplasia (p = 0.042). Posterior circulation severe stenosis was significantly associated with endovascular angioplasty (p < 0.001) and stenting (p= 0.030). Conclusions: Dizziness and vertigo were significantly correlated with hypoplasia/aplasia and tortuous posterior circulation. Age and sex were significantly correlated with posterior circulation disorder. Diabetes and cardiac disorders were significantly associated with severe stenosis, which needed endovascular procedures. The study was conducted in a cross-sectional design which warrants further prospective studies to establish the association.